2010
DOI: 10.3846/jeelm.2010.26
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Seasonal Variations of Hard Cosmic Ray Flux and Atmospheric Pressure in 2004–2005

Abstract: This paper focuses on the analysis of connection between changes in hard cosmic ray flux (HCRF) and atmospheric pressure. To analyse connection between HCRF and atmospheric pressure change, the data of HCRF were obtained using a gamma spectrometer. The statistical data of measurements have been analysed. Detailed information on atmospheric pressure was presented by the Lithuanian Hydrometeorological Service. Correlation coefficients were calculated by performing a simple linear regression analysis between HCRF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…The absence of any increase in the higher energy band indicates that the enhancement in our observations is solely due to the rainfall. Styro et al (2010) showed that the variation of hard cosmic ray flux and atmospheric pressure has a strong inverse correlation. They observed that atmospheric pressure decreases when a cyclone is in motion over the observation site, resulting in the reduced air density and hence more cosmic particles can reach the ground surface (Styro et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The absence of any increase in the higher energy band indicates that the enhancement in our observations is solely due to the rainfall. Styro et al (2010) showed that the variation of hard cosmic ray flux and atmospheric pressure has a strong inverse correlation. They observed that atmospheric pressure decreases when a cyclone is in motion over the observation site, resulting in the reduced air density and hence more cosmic particles can reach the ground surface (Styro et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Nishina et al (1940a) noted that the observed decrease in cosmic ray intensities is expected because of the temperature effect of the cosmic rays, for the northwest passage of a typhoon. Recently, Styro et al (2010) attempted to study the influence of cyclonic events on hard cosmic ray flux (HCRF) using NaI (Tl) scintillation detector for γ -ray spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The monitoring of hard cosmic rays flux (HCRF) was carried out by a gama -spectrometer with scintillation detector [17]- [21]. The detector of device made of crystal NaI(Tl) (6,3×6,3 cm) was covered with a lead protection of 12 cm thick to absorb the mild component of cosmic radiation (Styra et al2005).…”
Section: Methodsmentioning
confidence: 99%
“…However, because of their short lifetime (26 ns), π-mesons cover a short distance (about 125 m) and turn into muons with a lifetime of 2 μs (14). During this time, muons cannot reach the ground surface from the altitude of 15 km; therefore, their flux to the ground surface is registered from lower heights (15)(16)(17). So, near the ground surface, only the secondary cosmic flux takes place.…”
Section: Introductionmentioning
confidence: 99%